PSIKOEDUKASI TIME MANAGEMENT UNTUK MENURUNKAN STRES KERJA PADA KARYAWAN - Oedi Niesya Bella Ragazza (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Work stress is a psychological reaction that arises due to high work pressure and needs to be managed so that it does not have a negative impact on employee welfare. Time Management is a psychoeducational intervention that aims to help individuals develop full awareness of their current experiences to reduce reactivity to stressors. This study aims to determine the effectiveness of Time Management in reducing work stress among employees of an information technology consulting company. The research design used was a quasi-experimental pretest–posttest one group with 11 employees participating. The instrument used was the Perceived Stress Scale (PSS-10) to measure work stress levels. The intervention was conducted in two sessions focusing on training that included education on work stress, priority setting strategies, task planning, and reflection on the application of time management in the workplace. Data analysis was performed using the Wilcoxon test and showed significant results with an Asymp. Sig. (2-tailed) value of 0.003 (p < 0.05). These results indicate a significant difference between work stress levels before and after the intervention, marked by a decrease in stress scores among participants. The implications of this study emphasize the importance of implementing a Time Management program as a stress management strategy in technology-based work environments.